2019
DOI: 10.33116/ije.v2i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Bioavtur Synthesis from Palm Fatty Acid Distillate through Hydrotreating and Hydrocracking Processes

Abstract: Increasing concern in fossil fuel depletion and CO2 emissions create an urgent need for biofuel substitution. Bio-jet fuel is a possible alternative for conventional jet fuels which currently accounts for 2% of the world’s CO2 emission. Palm Fatty Acid Distillate (PFAD) is the byproduct of palm oil refinery process, which has a potential to become a promising raw material for the synthesis of bioavtur due to its high free fatty acid content. The oil-to-jet pathway is a possible route to produce bioavtur from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In this study, the production of hydrocarbons with high C 15 carbon chains was reported. The production was influenced significantly by 3% (wt.%) catalyst loading [2]. Also, other catalysts based on Ni-Mo/SiO 2 and NiMo/zeolite were also reported to increase BAF production and activity [3][4].…”
Section: ■ Introductionmentioning
confidence: 93%
“…In this study, the production of hydrocarbons with high C 15 carbon chains was reported. The production was influenced significantly by 3% (wt.%) catalyst loading [2]. Also, other catalysts based on Ni-Mo/SiO 2 and NiMo/zeolite were also reported to increase BAF production and activity [3][4].…”
Section: ■ Introductionmentioning
confidence: 93%
“…Indonesia is also actively engaged in the development of green fuels in various forms, including green diesel [36][37][38][39] , sustainable aviation fuels 40) , and green gasoline 38,41) . The production of these green fuels can capitalize on existing and under-construction refineries by utilizing the zeolite-based catalyst currently being developed by the Bandung Institute of Technology 42,43) .…”
Section: Biofuel Policiesmentioning
confidence: 99%
“…The crude palm oil (CPO) is then processed into a variety of derivative products in various industries such as the food, energy and cosmetics and cleaning products. In the energy industry, CPO is processed into biodiesel, gasoline and avtur [4]. Currently, the world is starting to shift towards new and renewable energy due to the depletion of fossil energy sources while energy needs are increasing.…”
Section: Introductionmentioning
confidence: 99%